Favoriser les apprentissages lexicaux dans les écoles isolées : la discussion lexicale à distance au cycle 3 (9-11 ans) - Anne Sardier (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This paper reports on a study entitled "Remote Schools Network (EER)", conducted in the department of Cantal (Auvergne, France). Our framework is the teaching of the lexicon : we analyse the effects of network discussions on the development of lexical acquisition by students aged 9 to 11. The role of verbal interactions in the teaching and learning of the lexicon is not often studied ; this is why we chose that perspective to study the effects of such discussions on learning. Discussions, as we understand them, are based, inter alia, on the semantic, syntagmatic and morphological features of the lexicon. They also take into account the specific characteristics of remote discussions (Develotte, Kern & Lamy, 2011). A comparative approach was set up involving both distant and non-distant "lexical discussions". Our results tend to underline the beneficial effects of these discussions on learning. Furthermore, they reveal similarities between distant and non-distant exchanges. They also confirm the existence of important differences in the process involved in the two types of discussions (distance vs presence).